Toward a methodology for studying leadership-as-practice - Joseph A. Raelin (Leadership, 2019)
This article is intended as a conceptual and practical foundation for those who wish to conduct research in the area of leadership-as-practice. Rather than offer a single methodology for studying how social and leadership activity is carried out in everyday life, it details a pluralistic set of methods and presents a series of theoretical guidelines through its phenomenological form of inquiry. In particular, it endorses discursive, narrative, ethnographic, aesthetic, and multimodal methods to attempt to capture concurrent, collective, and dialogical social practices. After providing an overview of praxis-oriented research as the methodological basis of leadership-as-practice, the article turns to the conceptual building blocks that can provide some guidance in selecting an appropriate methodology for study. These building blocks incorporate issues of agency, identity, materiality, context, power, and dialogue. The author hopes that researchers will take up the challenge of examining leadership dynamics “from within” to co-participate in working with actors engaged in projects of significance advance their mutual endeavors.
Keywords: J24; M12; M53; O15; 330; Methodology; Ethnography; Leadership-as-Practice; Action research; Phenomenology; Qualitative research